Cutaneous T-cell lymphomas: modern data of pathogenesis, clinics and therapy - O. M. Demina; O. E. Akilov; A. G. Rumyantsev (Онкогематология, 2018)
Cutaneous T-cell lymphomas (CTCL) are a heterogeneous group of extranodal non-Hodgkin’s lymphomas that are characterized by skin infiltration with malignant monoclonal T lymphocytes. More common in adults aged 55 to 60 years, the annual incidence is about 0.5 per 100 000 people. Mycosis fungoides, Sézary syndrome and CD30+ lymphoproliferative diseases are the main subtypes of CTCL. To date, CTCL have a complex concept of etiopathogenesis, diagnosis, therapy and prognosis. The article presented summary data on these issues.